Rekayasa Alat Pembuat Disk Runner Dengan Sistim Jig Dan Fixture - . Alfian; . Fardinal; . Islamiati; . Andri (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
Electrical energy at this time is needed in daily life so that the demand for power from the community is so large. PLN in this case as a provider of electric current is very overwhelmed to meet customer demand. For this reason, alternative energy producers called renewable energy are sought, one of which is a micro hydro plant. In West Sumatra alone, PLTMH has considerable potential to reach 500 MW (Source: PLN West Sumatra Regional Research and Development), so that West Sumatra itself has been designated a green energy barn by the Ministry of Energy and Mineral Resources (Source: Ministry of Energy and Mineral Resources). This is a promising prospect to be developed so that PLTMH equipment can be made with the mastery of appropriate technology. Based on the survey that has been done generally making microhydro turbines is still doing manual work with simple production equipment and very low production volume. The delay in making this generator is in the runner which has a disk component as a holder where the blade will produce rotation. Part made has a specific contour shape and repetitive work. Making disk runners through six workmanship sequences using different CAD applications, tools and places. Jig and Fixture is a technological tool that is suitable for manufacturing micro hydro turbine disk runners where the material holder is on the dividing plate while the torch weld cutter is hung on the guide for the cutting process. These assistive tools designed can eliminate the work process. This mobile device can cut circles with a diameter of 200 mm-300 mm, a blade of as many as 28 pieces with the same distance, shape profile and accuracy and meet the ergonomic aspects for the operator.